2016
DOI: 10.3171/2016.2.peds15475
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography–generated anthropometric measurements of orbital relationships in normal infants and children

Abstract: OBJECTIVE The aim of this study was to develop soft-tissue and bony anthropometric orbital measurements in a normal pediatric population based upon CT scans. METHODS This was a retrospective stratified study of children with ages ranging from birth to 36 months. Head CT images for 204 children were available and obtained with 0.625–1-mm slice widths. Soft-tissue and bone windows were reviewed. Images wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
14
2
Order By: Relevance
“…The difference is usually less than 1.5 mm with one exception being the breadth of the choanae at birth. Pool et al () report the interorbital distance at 0–3 months to be intermediate between the values in newborns and at 1–2 months of the present study. Contencin et al () found very similar nasal and choanal breadths in newborns (0.75 mm more and 0.22 mm less than in our study, respectively).…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…The difference is usually less than 1.5 mm with one exception being the breadth of the choanae at birth. Pool et al () report the interorbital distance at 0–3 months to be intermediate between the values in newborns and at 1–2 months of the present study. Contencin et al () found very similar nasal and choanal breadths in newborns (0.75 mm more and 0.22 mm less than in our study, respectively).…”
Section: Discussioncontrasting
confidence: 72%
“…Conversely, numerous studies have aimed to create normative values for craniofacial measurements to be used in medical practice (Brief et al, ; Delye et al, ; Dowgiallo, ; Escaravage & Dutton ; Hahn, Chu, & Cheung, ; Honn & Goz, ; Likus, Bajor, Gruszczyńska, Baron, & Markowski, ; Pool, Didier, Bardo, Selden, & Kuang, ; Stepanenko, ; Waitzman et al, ; including numerous X‐ray cephalometric studies, e.g., Broadbent, Broadbend, & Golden, ; Riolo et al, 1974; see also Hunter et al, ; Palomo & Broadbent, ). But despite this effort, growth trends of different regions of the facial skeleton in infancy and early childhood are still relatively poorly known.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,[8][9][10][11] Available data for the pediatric population is reported to a much lesser extent. [11][12][13] CT is now considered as the main technique for diagnosis, follow-up, and surgical planning for reconstructive surgery. There is literature that indicates that CT is more accurate and reliable than other cephalometric measures.…”
mentioning
confidence: 99%